Management of medical record in installation of inpatient regional public hospital Batara Guru Belopa - ., Musriati; ., Indar; Abdullah, Muhammad Tahir (International Journal Of Community Medicine And Public Health, 2019)
Background: This research is motivated by the high number of incompleteness of filling in the patient's medical record file in the inpatient installation, which is 30-35% in Regional Public Hospital Batara Guru Belopa. Methods: The research method is qualitative using the phenomenology approach. Determination of informants using purposive sampling method and obtained as many as eighteen informants. Data collection in the form of in-depth interviews, document review and observation. The validity of the data is done by triangulation and credibility test. Results: Management of medical records completeness seen from human resources who still need additional staffin the central part of the hospitalization by looking at the large number of patients and workload of the officers, doctors rarely fill in the full medical record sheets due to negligence of doctors due to other activities or in a hurry. Management of medical records completeness viewed from the procedure, there are still officers in the inpatient department who do not know the flow of exit and entry of the medical record file to the inpatient installation. The management of medical record completeness is seen from the information, implementation of hospital policy regarding the completeness of filling in medical record is not maximal because medical record file is slowly completed and returned to the medical record section. Conclusions: The hospital should be conducted a routine evaluation related to the completeness of the medical record and activated the hospital management information system (HMIS).